Influencer Politics: At the Intersection of Personal, Political, and Promotional - Arnesson, Johanna; Reinikainen, Hanna (De Gruyter Contemporary Social Sciences, 2024)
Social media influencers are seen as political and promotional actors in today's digital media. Some engage in specific causes, while others publicly support a particular party or ideology. Politicians may also socialize with influencers or adopt similar strategies. Drawing on examples from the Nordic countries, the promises and limitations of 'influencer policy' were discussed, and how political and promotional content coincide in culture.